Analysis of The Role of Metta Value in Building Early Childhood Character: A Literature Study - Susijati Susijati; Astri Chintya Astana; Tisya Permatasari (Interdisciplinary Social Studies, 2025)
The decline in national character, evidenced by various social problems, underscores the urgency of holistic and sustainable character education. The golden age of early childhood is a crucial phase for instilling fundamental values, as children at this age possess unique characteristics and are highly receptive to environmental stimuli. This literature review aims to analyze the role of Metta, a concept of universal loving-kindness from Buddhist teachings, in shaping the character of early childhood. The research method is a qualitative literature study, analyzing and synthesizing information from journal articles, books, and scientific sources related to Metta, child developmental psychology, and spirituality-based interventions. The analysis reveals that Metta is not merely a philosophical concept but a practical framework that can be implemented. The principles of Metta—such as loving-kindness, non-violence, and the wish for others' well-being—have a substantial link to the development of pro-social behavior, empathy, and emotional regulation in children. These findings are supported by studies on mindfulness-based interventions which show significant improvements in the social-emotional competence of preschoolers. This report also identifies Classroom Action Research (PTK) as an ideal methodology for empirically testing the effectiveness of Metta-based learning in the future. The proposed PTK framework is intended to serve as a guide for researchers and practitioners. The conclusion of this study is that Metta holds great potential as a foundation for early childhood character education and deserves consideration as a component of a comprehensive curriculum.